Long-Term Effects of Neonatal Single or Multiple Isoflurane Exposures on Spatial Memory in Rats - Murphy, Kathy L.; Baxter, Mark G. (Frontiers in Neurology, 2013)
General anesthetics are neurotoxic to neonatal rodents and nonhuman primates. Neonatal exposure to general anesthetics has been associated with long-term cognitive deficits in animal models. Some data from humans are consistent with long-term deleterious effects of anesthetic exposure early in life on cognitive development, with multiple exposures to general anesthetics being particularly damaging. We sought to determine whether repeated exposure of neonatal rats to anesthesia was associated with long-term cognitive impairments and whether the magnitude of impairments was greater than that resulting from a single exposure. Male or female Long-Evans rat pups were exposed to 1.8% isoflurane for 2 hours on postnatal day (P) 7, or for 2 hours each on P7, P10, and P13. Testing in a spatial working memory task began on P91. Rats that were repeatedly exposed to isoflurane were impaired relative to controls in the spatial working memory task. Male rats that received a single exposure to isoflurane showed an unexpected facilitation in spatial memory performance. These results support the hypothesis that multiple neonatal exposures to general anesthesia are associated with greater long-term cognitive impairment than a single exposure. The findings are congruent with human epidemiological studies reporting long-term cognitive impairments following multiple but not single general anesthetics early in life.